Tafsir tematik penciptaan manusia dalam prespektif al-qur’an, hadist, dan biologi - safitri, nadia dwi (Maliki Interdisciplinary Journal, 2025)
This article explores the creation of human beings through a thematic interpretation approach that integrates the perspectives of divine revelation (the Qur’an and Hadith) with modern science, particularly biology. The Qur’an and Hadith describe human creation through stages of nutfah, ‘alaqah, mudghah, followed by the infusion of the soul, reflecting the spiritual nature and honor of humans as stewards on Earth. Meanwhile, biology offers a scientific explanation through the theories of evolution and embryology, beginning from reproductive cells to the development of the fetus. The study highlights the coherence between revelation and science in understanding the origin of humans, despite their differing methodologies. Integrating religion and science is essential to achieve a comprehensive and harmonious understanding of human creation.